Digitalisering i sykepleietjenesten en arbeidshverdag i endring - Andreassen, Hege Kristin (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2019)
Our healthcare system is undergoing considerable transformation; standards are changing and established ways of working are being challenged. One change that has consequences for nursing services is increasing digitalization, with new information systems existing alongside paper-based and analogue systems. In this anthology, we have gathered contributions from researchers from a broad spectrum of disciplines and research traditions. Our objective has been to thematicize key perspectives on information and documentation work in the nursing profession during this period of increasing digitalization. We accomplish this objective by focusing on the changing role of the patient, nurses' record-keeping and important tools that have an impact on quality and collaboration in healthcare services.